Analysis of the constitutional court's decision number 116/puu-xxi/2023 concerning the parliamentary threshold as landmark decisions - Fratiwi, Andi; Muslim, Ikhwanul; Alhadi, Muhammad Nurcholis (Institute Of computer Science (IOCS), 2024)
This study analyzes the decision of the Constitutional Court Number 116/PUU-XXI/2023 regarding the parliamentary threshold as landmark decisions. This decision is evaluated whether it meets the criteria as landmark decisions. The purpose of this study is as a form of examination to find out whether the Constitutional Court decision No. 116/PUU-XXI/2023 can be said to be a landmark decision. This research uses a normative juridical method. The legal tools and materials used in this study include official documents related to the Constitutional Court decision Number 116/PUU-XXI/2023, including the text of the Constitutional Court's decision and legal arguments submitted by the parties involved in the dispute. In addition, this research will also refer to laws, constitutions, and other legal documents that are relevant in the context of constitutional law and politics in Indonesia. The data collection method used in this study is a literature study. The results of this study show that the Constitutional Court's decision Number 116/PUU-XXI/2023 cannot be said to be a landmark decision because it only meets three criteria. The first criterion does not contain new legal principles, namely in the judge's ruling stating that article 414 paragraph 1 of the conditional constitution, that the 4% parliamentary threshold remains in effect in the 2024-2029 elections, this means that there is no new legal principle. The new legal principle will apply in the 2029 House of Representatives elections and subsequent elections, as long as changes have been made. In the third criterion, the decision does not invalidate the entire law because in this case the election law is still valid, but the judge declared article 414 paragraph 1 of the constitution conditional.